2019
DOI: 10.1186/s13063-019-3394-4
|View full text |Cite
|
Sign up to set email alerts
|

Study protocol for a randomized, blinded, controlled trial of ketamine for acute painful crisis of sickle cell disease

Abstract: Background Sickle cell disease (SCD) is an inherited hematological disorder where the shape of red blood cells is altered, resulting in the destruction of red blood cells, anemia, and other complications. SCD is prevalent in the southern and eastern provinces of the Arabian peninsula. The most common complications for individuals with SCD are acute painful episodes that require several doses of intravenous opioids, making pain control for these individuals challenging. Instead of opioids, some stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Ketamine opioid-sparing effect has been demonstrated in some trials and retrospective studies mainly for ICU patients admitted for postoperative reasons and trauma [ 20 , 22 , 34 ]. In contrast, other trials did not show opioid-sparing effect [ 30 , 35 , 36 ] (Additional file 1 : Table S9). In our pilot, there was no difference in amount of sedatives or opioids and underlying reasons are likely multifactorial.…”
Section: Discussionmentioning
confidence: 93%
“…Ketamine opioid-sparing effect has been demonstrated in some trials and retrospective studies mainly for ICU patients admitted for postoperative reasons and trauma [ 20 , 22 , 34 ]. In contrast, other trials did not show opioid-sparing effect [ 30 , 35 , 36 ] (Additional file 1 : Table S9). In our pilot, there was no difference in amount of sedatives or opioids and underlying reasons are likely multifactorial.…”
Section: Discussionmentioning
confidence: 93%
“…We registered the trial protocol online (Clinicaltrials.gov registration NCT03431285) and, subsequently, published the full protocol. 34 All authors affirm the accuracy and completeness of the data and adherence to the approved protocol.…”
Section: Methodsmentioning
confidence: 83%
“…The fight against pain in SCD is studied on several approaches, including drugs already in use in the clinical routine such as Hydroxyurea, Pregabalin, Ketamine, as well as biological ones with blood transfusion and the development of new drugs such as crizanlizumab and of L-Glutamine. 14 , 15 , 16 , 17 , 18 , 19 , 20 In a double-blind, placebo-controlled study, crizanlizumab (humanized anti-P-selectin monoclonal antibody) showed promise as a medication to prevent VOC, although it did not show a reduction in the rate of hospitalization days. 18 , 19 In November 2019, this drug received FDA approval in the USA, being indicated to reduce the frequency of VOC in individuals aged ≥ 16 years and diagnosed with SCD.…”
Section: Discussionmentioning
confidence: 99%